Pengembaraan Ilmiah Dan Peran Syeikh Ahmad Khatib Al-Syambasi Dalam Penyebaran Islam Di Nusantara Melalui Thariqat Qadiriyyah Wa Naqsabdniyyah - Salman Al Farisi (Pusdikra Publishing, 2023)
This article attempts to describe the figure of the Nusantara scholar who belongs to the network of Middle Eastern scholars known as Ashabul Jawawyn, namely Sheikh Ahmad Khatib al-Sambasi, who has a very large role in spreading Islamic teachings. He is known as an expert in the field of Sufism and is called as a sufi expert, he is also known as the founder of the tarekat Qadiriyyah wa Naqsabandiyyah. In collecting data, the author refers to references in the form of books, journals, articles, and others that are relevant to the purpose of writing this article, and after the data is collected, the author sorts and selects the data used as a reference source and then describes the data collected. Obtained according to the purpose of the article in this paper, it was found that Sheikh Muhammad Ibn 'Abd Ghaffar al-Sambasi was an Indonesian scholar from West Kalimantan who wandered in search of Knowledge to the Haramyn Country at the age of 19, and lived in Mecca until he died in in 1875. Even so, Sheikh Ahmad Khatib al-Syambasi was known as someone who had a big role in the Islamic world, especially some areas of the Archipelago and Malaya, among the roles of Sheikh Ahmad Khatib al-Sambasi was to spread Islamic teachings through the Qadiryyah wa Naqsabandiyyah congregation, concerning to the book that is used as a reference in this tarekat is the book of Fath al-'Arifin, a book written by his students through the direct teaching of his teacher, Sheikh Ahmad Khatib al-Syambasi.